Hygienic maintenance in patients with maxillae atrophy and in oncological patients with maxillary resection rehabilitated with zygomatic implants: A nested monocentric prospective cohort study. - Pellegrino, Gerardo; Bertacci, Angelica; Relics, Daniela; Ferri, Agnese; Grande, Francesco; Felice, Pietro (International Journal of Dental Hygiene, 2024)
Objective: To assess peri‐implant soft tissues condition, comparing clinical parameters of implants placed in patients with atrophic upper jaws and patients who underwent maxillary resection for oncological reasons. Background: Zygomatic implants (ZIs) in oncologic patients could be affected by more complications compared to implants placed in atrophic maxillae. The soft tissue condition is an essential requirement for implant success, but few studies have investigated this topic. Methods: A nested monocentric prospective parallel cohort (atrophic vs. oncological patients) study was performed. Clinical visits and professional hygiene sessions were performed every three months, and bleeding on probing (BOP), probing pocket depth (PPD), gingival index (GI), plaque index (PI) and implant mobility were recorded by a blind outcome assessor. Results: In total, 77 ZIs placed in 21 patients were evaluated: 54 (70.1%) ZIs were inserted in patients belonging to the atrophic cohort (PAM) and 23 (29.9%) ZIs in the oncologic cohort (OP). The probability of having BOP at the considered mean follow‐up (27 months) was 24.8% (95% CI 19.0–31.9) for PAM and 22.9% (95% CI 15.1–33.9) OP. The mean PPD values were 2.78 ± 1.28 (range 1–8) in PAM and 2.91 ± 1.98 (range 0–10) in OP. None of the implants showed mobility. No associations between group belongingness and the entity of PPD, PI, GI and the risk of BOP were found, adjusting for the considered confounding factors (age, smoking and implant position). Conclusions: Under a strict supportive hygiene therapy protocol ZIs in oncologic patients showed similar peri‐implant tissue conditions to that of patients with maxillary atrophy.